Conservação, caracterização e atividade biológica de Croton grewioides Baill - Oliveira, Sara Dayan da Silva (2022)
Croton grewioides Baill. is a medicinal and aromatic plant that is widely used in folk medicine, with different proven biological activities. Due to its wide use and biological potential, this work aimed to carry out the genetic and morphoagronomic characterizations, and the evaluation of the in vitro antifungal activity of the essential oils of C. grewioides on phytopathogenic fungi. To evaluate the diversity and genetic structure of C. grewioides, 40 individuals were used in order to select the genotypes and to compose the species collection in an Active Germplasm Bank (BAG) when using SNP markers. Genotypes from two populations that were located in the states of Bahia and Sergipe were sampled. For the morphological characterization, 29 accessions that were kept in the C. grewioides collection of the Active Germplasm Bank of Medicinal and Aromatic Plants of the Federal University of Sergipe, Brazil, were used. Different essential oils (CGR104; CGR106; CGR112, and CGR126) and the major compounds (eugenol, methyl eugenol, and methyl chavicol) from C. grewioides were used to investigate its biological potential. For this, the methods of inhibition of mycelial growth, and the spore germination of the fungi Colletotrichum musae, and Fusarium solani in vitro were used. From the genetic diversity analysis, it was possible to estimate the observed and expected heterozygosities (Ho 0.211 < He 0.225), the Shannon Index (I: 0.357), the inbreeding coefficient (f: 0.056), and the number of exclusive alleles (Ae= BA: 1296 and SE: 799). The molecular analysis of variance (AMOVA) revealed greater genetic variations within the populations, and the discriminant principal components analysis (DAPC) allowed for the separation of the genotypes according to the population of origin (Bahia / Sergipe). Thirteen genotypes from the population of Sergipe and 17 from the population of Bahia were selected to compose the species collection. The morphological variables showed variability between the accessions, with the formation of 3 groups. The essential oils of C. grewioides were effective in mycelial control, demonstrating inhibitory effects (CGR112: 0.3%; CGR106, CGR112, and CGR104: 0.1%), and the fungicides (CGR126, CGR112, and CGR104: 0.05%; CGR126: 0.1%) and inhibiting inhibited the spore germination (CGR126 and CGR106: 0.2%) of C. musae and F. solani, respectively. Among the major compounds of the essential oils of C. grewioides, eugenol showed the best results in the activities tested. The results of diversity and genetic structure in this study provided essential information for the design of conservation strategies and the use of the species, evidencing the need for the conservation of the genotypes that were prospected in the two states, due to the greater proportion of the genetic variations being contained within the populations and the moderate genetic structuring between them. The phenotypic variability among the accessions of the C. grewioides collection can help in the development of strategies for the conservation and use of the species. The essential oils of C. grewioides have demonstrated to be promising alternatives in for the control of the phytopathogens C. musae and F. solani.